Paresthesias Among Community Members Exposed to the World Trade Center Disaster. Issue 4 (April 2017) - Marmor, Michael; Shao, Yongzhao; Bhatt, D. Harshad; Stecker, Mark M.; Berger, Kenneth I.; Goldring, Roberta M.; Rosen, Rebecca L.; Caplan-Shaw, Caralee; Kazeros, Angeliki; Pradhan, Deepak; Wilkenfeld, Marc; Reibman, Joan
Abstract : Objective: Paresthesias can result from metabolic disorders, nerve entrapment following repetitive motions, hyperventilation pursuant to anxiety, or exposure to neurotoxins. We analyzed data from community members exposed to the World Trade Center (WTC) disaster of September 11, 2001, to evaluate whether exposure to the disaster was associated with paresthesias. Methods: Analysis of data from 3141 patients of the WTC Environmental Health Center. Results: Fifty-six percent of patients reported paresthesias at enrollment 7 to 15 years following the WTC disaster. After controlling for potential confounders, paresthesias were associated with severity of exposure to the WTC dust cloud and working in a job requiring cleaning of WTC dust. Conclusions: This study suggests that paresthesias were commonly associated with WTC-related exposures or post-WTC cleaning work. Further studies should objectively characterize these paresthesias and seek to identify relevant neurotoxins or paresthesia-inducing activities.